Shipping Emissions in Ports - Merk, Olaf (International Transport Forum Discussion Papers, 2014)
Shipping could - in one way - be considered a relatively clean transport mode. This is particularly the case if one takes the angle of emissions per tonne-kilometre. Typical ranges of CO2 efficiencies of ships are between 0 and 60 grams per tonne-kilometre, this range is 20-120 for rail transport and 80-180 for road transport (IMO 2009). There is considerable variety between vessel types and CO2 efficiency generally increases with vessel size; e.g. CO2 emissions per tonne-km (in grams per year) for a container feeder ship (with capacity up to 500 TEU) were 31.6, three times higher than the emissions for Post Panamax container ships, with a capacity larger than 4,400 TEU (Psaraftis and Kontovas, 2008). This difference is even larger for dry bulk ships, with a difference of more than a factor 10 between the smallest vessels (up to 5000 dwt) and capsize vessels (> 120,000 dwt)